A method for increasing the surface adhesion of molecular sieve particles

By covering the oxide and hydroxide layer on the surface of the Cu-SSZ-13 molecular sieve catalyst, the problem of insufficient thermal stability and adhesion of the catalyst is solved, and the service life and purification efficiency are improved.

CN116139922BActive Publication Date: 2025-03-07CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211548425.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-03-07
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

The existing Cu-SSZ-13 molecular sieve catalysts can no longer meet the higher requirements for diesel vehicle exhaust purification in terms of thermal stability, high-active temperature window range and water resistance. Moreover, the surface adhesion of the molecular sieve is poor, easy to fall, affecting its service life.

Method used

The outer surface of the Cu-SSZ-13 molecular sieve is coated with an oxide layer and/or a hydroxide layer, including an oxide of silicon, an oxide of aluminum, an oxide of titanium, an oxide of zirconium and rare earth oxides, and a corresponding hydroxide layer, by atomic layer deposition.

Benefits of technology

It significantly improves the surface adhesion of the molecular sieve, reduces the risk of dropping, extends the service life of the catalyst, and does not affect the high-active temperature window of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003981113850000011
    Figure HDA0003981113850000011
  • Figure HDA0003981113850000012
    Figure HDA0003981113850000012
  • Figure HDA0003981113850000021
    Figure HDA0003981113850000021
Patent Text Reader

Abstract

The present invention provides a method for increasing the surface adhesion of molecular sieve particles, and an oxide layer and / or a hydroxide layer are coated on the outer surface of a Cu-SSZ-13 molecular sieve by an atomic layer deposition method; the oxide layer includes one or more of silicon oxide, aluminum oxide, titanium oxide, zirconium oxide and rare earth oxide; the hydroxide layer includes one or more of silicon hydroxide, aluminum hydroxide, titanium hydroxide, zirconium hydroxide and rare earth hydroxide. The present invention is aimed at the disadvantages that the molecular sieve catalyst has low surface adhesion and is easy to fall off after coating, and the molecular sieve is coated with an oxide layer and / or a hydroxide layer to improve the surface adhesion of the molecular sieve. It does not affect the high activity temperature window of the molecular sieve catalyst, reduces the risk of falling of the molecular sieve catalyst, and improves the service life of the catalyst, which has good application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for increasing the surface adhesion of molecular sieve particles. Background Art

[0002] Nitrogen oxides (NO x ) as the main air pollutant, causing great harm to production and life. x Among the emission pollution sources, NO x The largest number and the most serious harm. Therefore, most countries in the world have formulated strict laws and regulations on diesel vehicle exhaust emissions, and diesel vehicle companies have also installed exhaust purification devices on their diesel vehicles to meet regulatory requirements.

[0003] Currently, NH 3 -SCR technology to eliminate NO x , that is, urea solution is mixed into the exhaust gas of diesel vehicles, urea decomposes to produce ammonia, ammonia and NO x The reaction is carried out under the action of a catalyst to selectively reduce NO x Nitrogen and water. Before the implementation of the National VI B standard, NH 3 -SCR catalyst is mainly vanadium-tungsten-titanium catalyst, which has high NO x Eliminate efficiency.

[0004] However, as the implementation date of the National VI B emission standard approaches, higher requirements are placed on diesel vehicle exhaust purification. Existing vanadium tungsten titanium catalysts can no longer meet the requirements in terms of thermal stability, high activity temperature window range and water resistance. Cu ion-exchanged SSZ-13 molecular sieve (Cu-SSZ-13) has gradually replaced vanadium tungsten titanium catalysts as the main source of mobile NH 3 -SCR catalyst. However, when the molecular sieve and aluminum gel are mixed and directly coated on the cordierite honeycomb ceramic carrier, the molecular sieve has a smooth surface and poor adhesion, and it will fall off with a slight vibration, which seriously affects the service life of the molecular sieve catalyst. If the molecular sieve is sanded before coating, that is, the surface of the molecular sieve is scratched, although the surface adhesion of the molecular sieve can be appropriately increased, so that the molecular sieve can adhere better to the honeycomb ceramic. However, the molecular sieve will lose a large amount of low-temperature activity after sanding. Summary of the invention

[0005] The object of the present invention is to provide a method for increasing the surface adhesion of molecular sieve particles. The method of the present invention can make the molecular sieve have greater surface adhesion and effectively increase the service life of the catalyst.

[0006] The present invention provides a method for increasing the surface adhesion of molecular sieve particles, wherein an oxide layer and / or a hydroxide layer is coated on the outer surface of a Cu-SSZ-13 molecular sieve by an atomic layer deposition method;

[0007] The oxide layer includes one or more of silicon oxide, aluminum oxide, titanium oxide, zirconium oxide and rare earth oxide;

[0008] The hydroxide layer includes one or more of silicon hydroxide, aluminum hydroxide, titanium hydroxide, zirconium hydroxide and rare earth hydroxide.

[0009] Preferably, the coating layer on the outer surface of the Cu-SSZ-13 molecular sieve has a thickness of 0.1 to 1 nm.

[0010] Preferably, the mass ratio of the molecular sieve to the coating layer is (10000-50000):1.

[0011] Preferably, the atomic layer deposition comprises the following steps:

[0012] Under vacuum conditions, a precursor capable of forming a coating layer material and water vapor are alternately passed through the surface of the Cu-SSZ-13 molecular sieve, and nitrogen is purged, which is repeated 1 to 15 times.

[0013] Preferably, the temperature of the atomic layer deposition is 100-400°C.

[0014] Preferably, the method is used to improve the adhesion between the Cu-SSZ-13 molecular sieve and the honeycomb ceramic carrier.

[0015] Preferably, the honeycomb ceramic carrier is a cordierite honeycomb ceramic carrier.

[0016] The present invention provides a method for increasing the surface adhesion of molecular sieve particles. By atomic layer deposition, an oxide layer and / or a hydroxide layer is coated on the outer surface of a Cu-SSZ-13 molecular sieve; the oxide layer includes one or more of silicon oxide, aluminum oxide, titanium oxide, zirconium oxide and rare earth oxide; the hydroxide layer includes one or more of silicon hydroxide, aluminum hydroxide, titanium hydroxide, zirconium hydroxide and rare earth hydroxide. The present invention aims at the disadvantages of low surface adhesion of molecular sieve catalyst and easy falling after coating, and coats the molecular sieve with one or more of silicon oxide or silicon hydroxide, aluminum oxide or aluminum hydroxide, titanium oxide or titanium hydroxide, zirconium oxide or zirconium hydroxide, rare earth oxide or rare earth ion hydroxide to improve the surface adhesion of the molecular sieve. It does not affect the high activity temperature window of the molecular sieve catalyst, reduces the risk of falling of the molecular sieve catalyst, and increases the service life of the catalyst, which has good application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0018] Figure 1 The Cu-SSZ-13 molecular sieve catalyst in Example 1 of the present invention before and after coating has NO x Elimination activity comparison;

[0019] Figure 2 The Cu-SSZ-13 molecular sieve catalyst in Example 1 of the present invention is subjected to NO after hydrothermal aging before and after coating. x Elimination activity comparison;

[0020] Figure 3 The figure is a comparison of the surface adhesion of the Cu-SSZ-13 molecular sieve catalyst before and after coating in Example 1 of the present invention, wherein Figure a is before coating and Figure b is after coating. DETAILED DESCRIPTION

[0021] The present invention provides a method for increasing the surface adhesion of molecular sieve particles, wherein an oxide layer and / or a hydroxide layer is coated on the outer surface of a Cu-SSZ-13 molecular sieve by an atomic layer deposition method;

[0022] The oxide layer includes one or more of silicon oxide, aluminum oxide, titanium oxide, zirconium oxide and rare earth oxide;

[0023] The hydroxide layer includes one or more of silicon hydroxide, aluminum hydroxide, titanium hydroxide, zirconium hydroxide and rare earth hydroxide.

[0024] The present invention effectively improves the adhesion between the Cu-SSZ-13 molecular sieve and the cordierite honeycomb ceramic carrier through the above-mentioned method of coating the oxide layer and / or hydroxide layer on the surface of the molecular sieve particles, reduces the falling phenomenon of the molecular sieve catalyst due to vibration during use, can effectively increase the service life of the catalyst, and does not affect the high activity temperature window of the molecular sieve catalyst.

[0025] In the present invention, the coating method is specifically as follows:

[0026] The Cu-SSZ-13 molecular sieve is placed in an atomic layer deposition device. Under vacuum conditions, the raw material gas and water vapor required for deposition of the coating layer are alternately passed through the surface of the molecular sieve, and nitrogen is used for purging. This is repeated 1 to 15 times to obtain a Cu-SSZ-13 molecular sieve with a coating layer.

[0027] In the present invention, the source of the Cu-SSZ-13 molecular sieve is not particularly limited, and conventional commercially available Cu-SSZ-13 molecular sieves can be used. In the present invention, the particle size of the Cu-SSZ-13 molecular sieve is preferably 100 nm to 4 μm, more preferably 500 nm to 2 μm.

[0028] In the present invention, the temperature of the atomic layer deposition is preferably 100-400°C, more preferably 200-300°C, such as 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, preferably a range value with any of the above values ​​as the upper or lower limit. The different temperatures of the atomic layer deposition can obtain oxides and / or hydroxides, such as deposition at 100°C, theoretically all hydroxides, and deposition above 300°C, theoretically all oxides, but since the surface of the deposited oxide coating layer will also have some hydroxyl groups, the present invention does not make a special distinction for this.

[0029] In the present invention, the raw material gas of the material to be coated is preferably a precursor such as trimethylaluminum, siloxane, titanium tetrachloride, etc., which can form corresponding oxides or hydroxides during the atomic layer deposition process.

[0030] In the present invention, the coating method can be a single-layer coating or a multi-layer alternating coating. In the multi-layer coating, it can be a repeated multi-layer coating using one coating deposition material, or it can be a multi-layer deposition coating using multiple coating deposition materials. The atomic layer deposition process of each layer can repeat the above atomic layer deposition process. The present invention has no special restrictions on the multi-layer combination of different types of coating deposition material layers. For example, for a coating layer using two coating deposition materials, an ABAB coating method or an AABB coating method can be adopted; for a coating layer using three coating deposition materials, an ABCABC coating method or an AABBCC coating method can be adopted, and so on.

[0031] In the present invention, the Cu-SSZ-13 molecular sieve with a coating layer prepared according to the above method can be used for NO in diesel vehicle exhaust. x The purification can reduce the falling phenomenon of molecular sieve catalyst due to vibration during use and greatly extend the service life of the catalyst.

[0032] The present invention provides a method for increasing the surface adhesion of molecular sieve particles. By atomic layer deposition, an oxide layer and / or a hydroxide layer is coated on the outer surface of a Cu-SSZ-13 molecular sieve; the oxide layer includes one or more of silicon oxide, aluminum oxide, titanium oxide, zirconium oxide and rare earth oxide; the hydroxide layer includes one or more of silicon hydroxide, aluminum hydroxide, titanium hydroxide, zirconium hydroxide and rare earth hydroxide. The present invention aims at the disadvantages of low surface adhesion of molecular sieve catalyst and easy falling after coating, and coats the molecular sieve with one or more of silicon oxide or silicon hydroxide, aluminum oxide or aluminum hydroxide, titanium oxide or titanium hydroxide, zirconium oxide or zirconium hydroxide, rare earth oxide or rare earth ion hydroxide to improve the surface adhesion of the molecular sieve. It does not affect the high activity temperature window of the molecular sieve catalyst, reduces the risk of falling of the molecular sieve catalyst, and increases the service life of the catalyst, which has good application value.

[0033] In order to further illustrate the present invention, a method for increasing the surface adhesion of molecular sieve particles provided by the present invention is described in detail below in conjunction with examples, but it should not be construed as limiting the scope of protection of the present invention.

[0034] Example 1: Coating aluminum hydroxide alone.

[0035] Take 500 g of Cu-SSZ-13 molecular sieve, load it into the atomic layer deposition equipment, evacuate it, and heat it to 300° C. Pass trimethylaluminum and water vapor alternately on the surface of the molecular sieve, and purge it with nitrogen, and repeat 8 times.

[0036] Aging test:

[0037] The Cu-SSZ-13 molecular sieve catalyst coated with an aluminum hydroxide coating layer was aged for 100 hours at 650° C. and 10% water vapor to obtain a molecular sieve and aluminum oxide coating layer catalyst after high temperature hydrothermal aging.

[0038] Example 2: Simultaneous coating of aluminum and silicon hydroxides in an ABAB manner.

[0039] 500 g of Cu-SSZ-13 molecular sieve was loaded into an atomic layer deposition apparatus, vacuumed, and heated to 300° C. Trimethylaluminum, water vapor, siloxane, and water vapor were alternately passed over the surface of the molecular sieve, and purged with nitrogen, and this was repeated 4 times.

[0040] Aging test:

[0041] The Cu-SSZ-13 molecular sieve catalyst coated with an aluminum silicon hydroxide coating layer was aged for 100 hours at 650° C. and 10% water vapor to obtain a molecular sieve and an aluminum silicon oxide coating layer catalyst after high temperature hydrothermal aging.

[0042] Example 3: Simultaneous coating of aluminum and silicon hydroxides in an AABB manner.

[0043] Take 500g of Cu-SSZ-13 molecular sieve, load it into the atomic layer deposition equipment, evacuate it, and heat it to 200°C. Pass trimethylaluminum and water vapor alternately on the surface of the molecular sieve and purge it with nitrogen, repeat twice, then pass siloxane and water vapor alternately on the surface of the molecular sieve and purge it with nitrogen, repeat twice.

[0044] Aging test:

[0045] The Cu-SSZ-13 molecular sieve catalyst coated with an aluminum silicon hydroxide coating layer was aged for 100 hours at 650° C. and 10% water vapor to obtain a molecular sieve and an aluminum silicon oxide coating layer catalyst after high temperature hydrothermal aging.

[0046] Example 4: Simultaneous coating of aluminum, silicon and titanium hydroxides in an ABCABC manner.

[0047] Take 500g of Cu-SSZ-13 molecular sieve, load it into the atomic layer deposition equipment, evacuate it, and heat it to 100°C. Pass trimethylaluminum, water vapor, siloxane, water vapor, titanium tetrachloride and water vapor alternately on the surface of the molecular sieve, and purge it with nitrogen, repeating once.

[0048] Aging test:

[0049] The Cu-SSZ-13 molecular sieve catalyst coated with an aluminum silicon titanium hydroxide coating layer was aged for 100 hours at 650° C. and 10% water vapor to obtain a molecular sieve and an aluminum silicon oxide coating layer catalyst after high temperature hydrothermal aging.

[0050] Example 6: Simultaneous coating of aluminum, silicon and titanium hydroxides by AABBCC method.

[0051] Take 500g of Cu-SSZ-13 molecular sieve, load it into the atomic layer deposition equipment, evacuate it, and heat it to 400℃. Pass trimethylaluminum and water vapor alternately on the surface of the molecular sieve, and purge it with nitrogen, repeat twice, then pass siloxane and water vapor alternately on the surface of the molecular sieve, and purge it with nitrogen, repeat twice. Then pass titanium tetrachloride and water vapor alternately on the surface of the molecular sieve, and purge it with nitrogen, repeat twice.

[0052] Aging test:

[0053] The Cu-SSZ-13 molecular sieve catalyst coated with an aluminum silicon titanium hydroxide coating layer was aged for 100 hours at 650° C. and 10% water vapor to obtain a molecular sieve and an aluminum silicon titanium oxide coating layer catalyst after high temperature hydrothermal aging.

[0054] Figure 1 The Cu-SSZ-13 molecular sieve catalyst in Example 1 of the present invention before and after coating has NO x The elimination activity comparison is Figure 1 It can be seen that the method for improving the molecular sieve catalyst of the present invention does not affect the high activity temperature window of the catalyst.

[0055] Figure 2 The Cu-SSZ-13 molecular sieve catalyst in Example 1 of the present invention is subjected to NO after hydrothermal aging before and after coating. x The elimination activity comparison is Figure 2 It can be seen that after aging for 100 hours at 650 degrees with 10% water vapor, the molecular sieve catalyst containing the coating layer maintains a very high catalytic activity.

[0056] Figure 3 The surface adhesion of the Cu-SSZ-13 molecular sieve catalyst before and after coating in Example 1 of the present invention is compared. Figure 3 It can be seen that the improved method of the present invention for molecular sieve catalyst significantly improves the adhesion of the molecular sieve surface. The maximum adhesion of the surface before the molecular sieve is coated is 150nN, and the minimum adhesion of the surface after the molecular sieve is coated is 40000nN, and the average adhesion is increased by 1500 times.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of Cu-SSZ-13 molecular sieve particles coated with an oxide layer and / or a hydroxide layer on the surface to improve the adhesion between the Cu-SSZ-13 molecular sieve and a cordierite honeycomb ceramic carrier, wherein the surface-coated Cu-SSZ-13 molecular sieve particles are coated with an oxide layer and / or a hydroxide layer on the outer surface of the Cu-SSZ-13 molecular sieve by an atomic layer deposition method; The oxide layer includes one or more of silicon oxide, aluminum oxide and titanium oxide; The hydroxide layer includes one or more of silicon hydroxide, aluminum hydroxide and titanium hydroxide; The atomic layer deposition comprises the following steps: Under vacuum conditions, a precursor capable of forming a coating layer material and water vapor are alternately passed through the surface of the Cu-SSZ-13 molecular sieve, and nitrogen is purged, and the process is repeated 1 to 15 times; The temperature of the atomic layer deposition is 100-400°C.

2. The use according to claim 1, characterized in that: The thickness of the coating layer on the outer surface of the Cu-SSZ-13 molecular sieve is 0.1-1 nm.

3. The use according to claim 2, characterized in that: The mass ratio of the molecular sieve to the coating layer is (10000~50000):1.

Citation Information

Patent Citations

  • Denitration catalyst and preparation method thereof

    CN112371163A

  • Surface-treated silicoaluminophosphate molecular sieve

    US20200330966A1